Review of Second language pronunciation assessment: Interdisciplinary perspectives; Editors: Talia Isaacs, Pavel Trofimovich; Publisher: Multilingual Matters (Second Language Acquisition series), 2017; ISBN: 9781783096848 (hbk), 9781783096831 (pbk), 9781783096855 (pdf), 978783096862 (ebuk); Pages: 273 - Waniek-Klimczak, Ewa (Studies in Second Language Learning and Teaching, 2018)
.